2016
DOI: 10.1161/hypertensionaha.116.07201
|View full text |Cite
|
Sign up to set email alerts
|

Morning and Evening Home Blood Pressure and Risks of Incident Stroke and Coronary Artery Disease in the Japanese General Practice Population

Abstract: Our aim is to determine the optimal time schedule for home blood pressure (BP) monitoring that best predicts stroke and coronary artery disease in general practice. The Japan Morning Surge-Home Blood Pressure (J-HOP) study is a nationwide practice-based study that included 4310 Japanese with a history of or risk factors for cardiovascular disease, or both (mean age, 65 years; 79% used antihypertensive medication). Home BP measures were taken twice daily (morning and evening) over 14 days at baseline. During a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 36 publications
5
155
2
3
Order By: Relevance
“…8 Furthermore, morning SBP surge is directly related to 24-h SBP variability and future cardiovascular events. 9 Prior research found morning SBP surge to be associated with stroke events independently of nocturnal BP falls and 24-h SBP in hypertensive patients.…”
mentioning
confidence: 99%
“…8 Furthermore, morning SBP surge is directly related to 24-h SBP variability and future cardiovascular events. 9 Prior research found morning SBP surge to be associated with stroke events independently of nocturnal BP falls and 24-h SBP in hypertensive patients.…”
mentioning
confidence: 99%
“…Among these, the Japan Morning Surge-Home Blood Pressure study aimed to determine the optimal time schedule for HBPM to best predict stroke and coronary artery disease in over 4000 Japanese people with a history of, or risk factors for, CVD [22]. During a mean follow-up of 4 years, morning SBP was shown to improve the discrimination of incident stroke beyond traditional risk factors including office SBP; as such, the authors concluded that morning home SBP itself should be evaluated to ensure best stroke prediction in clinical practice.…”
Section: Recommendationmentioning
confidence: 99%
“…4,5 Four Asian studies have demonstrated that morning home BP is a better prognostic predictor of cardiovascular events than clinic BP. These were the general population-based Ohasama Study, 32 the general practitioner-based J-HOP study (Japan Morning Surge-Home Blood Pressure), 33 a hypertensive outpatient trial on medication (HOMED-BP, Hypertension Objective Treatment Based on Measurement by Electrical Devices of Blood Pressure), 34 and the largest nationwide Japanese real-world observational study (HONEST). 7,35 Indeed, in the HONEST study, a morning home SBP of ≈125 mm Hg was associated with minimal risk for both stroke and coronary artery disease events.…”
Section: Facilitation Of a Home Bp-guided Approach In Asiamentioning
confidence: 99%